2010
DOI: 10.1007/s10528-010-9404-6
|View full text |Cite
|
Sign up to set email alerts
|

Role of HLA Allele Polymorphism in Chronic Hepatitis B Virus Infection and HBV Vaccine Sensitivity in Patients from Eastern Turkey

Abstract: Human leukocyte antigen (HLA) alleles have been associated with the clinical outcomes of hepatitis B virus (HBV) infection, which range from spontaneous recovery to hepatocellular carcinoma. In this study involving subjects from eastern Turkey, the frequencies of HLA-B35, HLA-CW4, HLA-DQ2, and HLA-DQ8 were markedly higher in the chronic HBV group than those in the spontaneously recovered group; the frequencies of HLA-A11 and HLA-A24 in the nonresponsive HBV vaccine group were markedly higher than those in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 45 publications
1
23
0
1
Order By: Relevance
“…These 18 articles were published from 1995 to 2011 with 15 in English [16,[18][19][20][21][32][33][34][35][36][37][38][39][40][41] and three in Chinese [42][43][44] . Of them, nine studies were on Han Chinese populations [19][20][21][34][35][36][42][43][44] and 10 studies on other race (Gambia [32] , Caucasian [16] , Korean [18,37,39] , Iran [33,40] , Thai [38] and Turkish [41] ). Besides, one publication contained two individual case-control studies from two different ethnic populations (Chinese Han and Taiwanese aborigines [19] ).…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…These 18 articles were published from 1995 to 2011 with 15 in English [16,[18][19][20][21][32][33][34][35][36][37][38][39][40][41] and three in Chinese [42][43][44] . Of them, nine studies were on Han Chinese populations [19][20][21][34][35][36][42][43][44] and 10 studies on other race (Gambia [32] , Caucasian [16] , Korean [18,37,39] , Iran [33,40] , Thai [38] and Turkish [41] ). Besides, one publication contained two individual case-control studies from two different ethnic populations (Chinese Han and Taiwanese aborigines [19] ).…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
“…Jiang et al [21] (2003) Wu et al [19] (2004) Zhang et al [34] (2006) Yang et al [35] (2007) Zhu et al [36] [32] (1995) Hohler et al [16] (1997) Ahn et al [18] (2000) Akcam et al [33] (2002) Wu et al [19] (2004) Hwang et al [37] (2007) Cho et al [39] (2008) Remezami et al [40] (2008) Albayrak et al [41] …”
Section: Chinese Hanmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, convincing studies about association between MHC class I and HBV persistence are rare. However, Albayrak et al (2011) showed that HLA-B35 and HLA-CW4 were important risk factors in Turkey population. Chinese reports showed that HLA-B*4001 was not related to the HBV clearance but had an effect in Taiwan populations (Wu et al, 2004).…”
Section: Hlamentioning
confidence: 99%
“…Recently, a genome-wide association study demonstrated that genetic variants in the HLA-DP locus were strongly associated with chronic hepatitis B in Japanese and Thai populations (14). In addition, Albayrak et al found that the role of HLA allele polymorphism was associated with the progression to chronic HBV infection in eastern Turkey, and that HBV infection is different in different racial populations (15).…”
Section: H Epatitis B Virus (Hbv) Infection Is a Worldwidementioning
confidence: 99%